Pengaruh Kepemimpinan, Pelatihan, Motivasi Kerja Terhadap Kinerja Karyawan pada PT. Patco Elektronik Teknologi - Karsih, Karsih; Gunawan, Ahmad; Maharani, Meilia; Putri, Agustina Mulia (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This research investigates how the performance of PT Patco Elektronik Teknologi employees is influenced by leadership, training and work motivation. The survey used was a questionnaire distributed to employees. The results of the analysis show that good leadership improves employee performance because an inspirational leader can motivate the team to achieve common goals. In addition, systematic and relevant training improves employee skills and knowledge, which results in increased productivity. Apart from that, work motivation is also proven to have an effect, because motivated employees show better performance. The results show that good leadership, appropriate training programs, and high motivation are important components in improving employee performance. PT Patco Elektronik Teknologi management must create ongoing leadership and training programs to improve performance.